The US Deprescribing Research Network: a network to catalyze deprescribing science - Shahroodi, Raha; Norton, Jonathan D.; Boyd, Cynthia M.; Steinman, Michael A. (Frontiers in Medicine, 2025)
Deprescribing plays a critical role in ensuring safe and effective healthcare for older adults, including but not limited to those with vulnerabilities such as multimorbidity and dementia, which increase the risk of harm from unnecessary medications. However, much is unknown on how to safely and effectively stop medications. In response, the US Deprescribing Research Network (USDeN) was created with a mission of enhancing the quality, volume, and real-world impact of research aimed at optimizing medication use among older adults. This Perspective explores the rationale for its creation, the principles and ideas that animate its work, its impacts on research, and future directions for deprescribing research. By advancing research in this area, we aim to improve healthcare outcomes and reduce medication-related harm among older adults.